2005
DOI: 10.1021/bi051155s
|View full text |Cite
|
Sign up to set email alerts
|

The Structure−Activity Relationship of Ferric Pyoverdine Bound to Its Outer Membrane Transporter:  Implications for the Mechanism of Iron Uptake

Abstract: Under iron limitation, Pseudomonas aeruginosa ATCC 15692 secretes a major siderophore, pyoverdine I (PvdI). This molecule chelates iron in the extracellular medium and shuttles it into the cells via a specific outer membrane transporter, FpvAI. PvdI consists of a fluorescent chromophore derived from 2,3-diamino-6,7-dihydroxyquinoline and containing one of the bidentate groups involved in iron chelation, linked to a peptide moiety containing the two other bidentate groups required for binding to Fe(3+). Kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 45 publications
(115 reference statements)
4
30
0
Order By: Relevance
“…It is only able to bind the Pvd shown in Fig. 1a and a similar Pvd produced by a strain of P. fluorescens (Schons et al 2005). In FpvA-Pvd-Fe, Pvd-Fe is attached to the plug domain via the chromophore (Fig.…”
Section: Ferripyoverdine Bindingmentioning
confidence: 98%
See 2 more Smart Citations
“…It is only able to bind the Pvd shown in Fig. 1a and a similar Pvd produced by a strain of P. fluorescens (Schons et al 2005). In FpvA-Pvd-Fe, Pvd-Fe is attached to the plug domain via the chromophore (Fig.…”
Section: Ferripyoverdine Bindingmentioning
confidence: 98%
“…The peptide moiety, which determines the receptor specificity of the Pvd, interacts mainly with the b-barrel domain and the extracellular loops, rather than with the plug domain (Wirth et al 2007). Binding studies with different Pvd analogues have shown that Ser 1 and the succinyl moiety linked to the chromophore of Pvd can be sterically hindered with no effect on binding or the iron uptake properties of Pvd-Fe (Schons et al 2005). However, the second position of the peptide moiety in Pvd (Arg) cannot be subject to steric hindrance without a major decrease in affinity of the ferric-siderophore (Schons et al 2005).…”
Section: Ferripyoverdine Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…We introduced a primary amine to Pvd via a PEG linker on the succinate moiety in order to be able to immobilize Pvd to a Biacore sensor chip by primary amine coupling. The succinate moiety was chosen as the attachment site because it has been previously demonstrated that the attachment of bulky groups to this part of Pvd had no effect on iron chelation and transport (27). Using the immobilized Pvd surface, we were able to compare the affinities of FpvA for Pvd and Pvd-Fe in a controlled and quantitative manner.…”
Section: Purified Fpva Binding To Pvd Is Metal Dependent In Vitromentioning
confidence: 99%
“…Apo-pyoverdine was described to be bound to the surface of the FpvA receptor in a pocket lined with aromatic residues (3,13,17). It has therefore been proposed that iron-loaded pyoverdine can exchange with unloaded pyoverdine at the surface of the receptor, a process which is dependent on the inner membrane protein TonB, which relays the proton motive force to FpvA (16). Here, Greenwald et al reveal that in reality apo-pyoverdine has no affinity at all for the FpvA receptor and that the previously observed fluorescence rather is due to the association of Al-pyoverdine with the receptor, meaning that the interactions measured by fluorescent resonance energy transfer are in fact those occurring between Al-pyoverdine and FpvA (12,13).…”
Section: Mechanism Of Ferripyoverdine Uptakementioning
confidence: 99%